2001
DOI: 10.1016/s1010-7940(01)00900-9
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis carinii pneumonia in heart transplant recipients

Abstract: The frequency of PC pneumonia among HT patients is the same as the frequency of PC infection in the general population. This observation and the long interval between transplantation and the development of PC pneumonia observed in the study support the hypothesis that the occurrence of PC pneumonia in immunocompromised patients might be from a new infection rather than from the reactivation of latent organisms. Therefore, continuous prophylaxis might be indicated in areas with a high prevalence of PC for patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…association with this condition [28] . Except for some isolated reports, numerous studies have established the efficacy and safety of TMP/SMX prophylaxis [23,37,38] . Generally, although TMP/SMX is well tolerated, serious side effects have also been tolerated during its use [39,40] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…association with this condition [28] . Except for some isolated reports, numerous studies have established the efficacy and safety of TMP/SMX prophylaxis [23,37,38] . Generally, although TMP/SMX is well tolerated, serious side effects have also been tolerated during its use [39,40] .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast with these positive findings for MMF, Arichi et al [22] suggested that administration of MMF may represent a risk factor for PCP in patients undergoing renal transplantation due to strong immunosuppression. Cardenal et al [23] compared 72 CT patients with a group of subjects representative of the normal population during an average follow up duration of 5 years and showed a similar frequency of PCP in both groups. While the causative agent was associated with opportunistic infections, it was associated with subclinical infection in the normal subjects [23] .…”
Section: Thi Incidence Of Pcp In Patients Undergoing Cardiac Transplamentioning
confidence: 99%
See 1 more Smart Citation
“…85 Protozoa In heart transplant recipients, the reported incidence of Pneumocystis carinii pneumonia ranges from less than 1% to 10%. 78,86 Toxoplasma Gondii Infection Toxoplasmosis following heart transplantation is the result of reactivation of latent disease in the seropositive donor heart and because of the predilection of the parasite to invade muscle tissue. T. gondii usually causes central nervous system infections and is treated with pyrimethamine with sulfadiazine or clindamycin.…”
Section: Mucocutaneous Candidiasismentioning
confidence: 99%
“…Early-onset Pneumocystis carinii pneumonia complicating Norwood II operation in a 3-month-old patient Sir: In the field of cardiac surgery Pneumocystis carinii pneumonia (PCP) is well known as an opportunistic infection after heart transplantation [1,4], but it is not usually known to cause early postcardiotomy pneumonia. In adults PCP arises preferentially from new infections [1].…”
mentioning
confidence: 99%